Treatment Of Class Iı Dıvısıon Iı Malocclusıon Wıth A' Combınatıon Of Twınb-Lock And Edgewıse Technıques - Hüseyin Ölmez; Deniz Sağdıç; Osman Bengi (Galenos Yayinevi, 1994)
In this article, the use of a combination of functional appliance and Edgewise-Technique for teratment of Class II Division II malocclusion is presented. While the skeletal disorders are improved with Twin Block appliance, the dental anomalies can he treated with Edgewise Technique Therapies, by this combined technique.